2018
DOI: 10.1016/j.matdes.2018.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive pressure sensors employing 3C-SiC nanowires fabricated on a free standing structure

Abstract: This paper presents highly sensitive pressure sensors using piezoresistive nanowires. Our approach is based on nanowires locally fabricated on free standing structures with a high strain concentration. This strain concentration phenomenon amplifies the strain induced into nano-scaled sensing elements while the bulk materials are still at small strain regime, therefore enhancing the sensitivity of the sensors. For proof of concept, we utilized SiC nanowire fabricated using focused ion beam from an epitaxially g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Silicon carbide (SiC) is a large bandgap material with high electron mobility and chemical inertness, enabling its applications in pressure, gas, and temperature sensors. Given the high temperature and inert conditions, Zank and co‐workers and other group discovered that siloxane polymers could be converted into SiC.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbide (SiC) is a large bandgap material with high electron mobility and chemical inertness, enabling its applications in pressure, gas, and temperature sensors. Given the high temperature and inert conditions, Zank and co‐workers and other group discovered that siloxane polymers could be converted into SiC.…”
Section: Introductionmentioning
confidence: 99%
“…[256][257][258][259][260] However, the fabrication of high-performance pressure sensors based on WBG semiconductor nanowires, especially for SiC, group III-nitrides, and diamond, are very rare. [261][262][263] For instance, Phan et al reported an effective approach to develop highly sensitive pressure sensors employing 3C-SiC nanowires fabricated at the center of a dogbone-like structure. [261] Figure 12a shows a photograph of SiC nanowire-based pressure sensors mounted on an acrylic holder.…”
Section: Pressure Sensorsmentioning
confidence: 99%
“…[1][2][3] The advantages result from the high energy bandgap, mechanical strength, chemical inertness, and the high melting point of SiC. [4][5][6] Therefore, a wide range of SiC-based microsensing/electronics devices have been developed with several micromachining techniques. [7,8] Unlike silicon counterparts, SiC micromachining processes are undoubtedly limited and expensive due to the chemical inertness of SiC.…”
Section: Introductionmentioning
confidence: 99%